Entrepreneurs: in the dilemma of being of having to be - Herrera Domínguez, Marypaz; García Sierra, Margarita R; Velaco Díaz, Blanca E. (2021)
This work includes a diagnosis of the micro, small and entrepreneurial companies; in the framework of the knowledge era, the systems, the post-capitalism and the exhaustion of neoliberalism; it analyzes proposals of international organisms as generators of employment and welfare for society, also emphasizes the difference between undertaking by necessity or alternative to unemployment and the undertaking of opportunity. It reviews the theory of subjective welfare applied in the training of a group of entrepreneurs, to conclude that strengthening the human side is an excellent alternative to consolidate their projects and bring them to a stage of growth.